Primerjava med dvema novelama: med Primoža Kozaka Ano in Edvarda Kocbeka Črno orhidejo - Kermauner, Taras (Slavistična revija, 2006)
Comparing the novellas Ana and Črna orhideja (the former was written in 1949m the latter waspublished in 1951), the author attempt to find their common elements - i.e., the topics of the liquidation of a female gestapo collaborator, the love of both Partisan commanders towards her, and their execution of her - and the elements that separate them, i.e., their theology, philosophy, and ethics.
Keywords: človek; fate; fear; guilt; Kocbek, Edvard; Kozak, Primož; krivda; ljubezen; love; man; novela; Slovene literature; slovenska književnost; slovenska proza; strah; usoda